Beauty and Holiness the Dialogue Between Aesthetics and Religion. - Martin, James Alfred (Princeton : Princeton University Press, 2014)
In this broad historical and critical overview based on a lifetime of scholarship, James Alfred Martin, Jr., examines the development of the concepts of beauty and holiness as employed in theories of aesthetics and of religion. The injunction in the Book of Psalms to ""worship the Lord in the beauty of holiness"" addressed a tradition that has comprehended holiness primarily in terms of ethical righteousness--a conception that has strongly influenced Western understandings of religion. As the author points out, however, the Greek forbears of Western thought, as well as many Eastern traditio.
Cover; Contents; The Bible; Plato; Aristotle; Augustine; Thomas Aquinas; Jonathan Edwards; Hume; Kant; Schiller; Schlegel; Schelling; Schleiermacher; Hegel; Otto; Eliade; Van Der Leeuw; Tillich; Geertz; Santayana; Dewey; Whitehead; Heidegger; Wittgenstein; India; China; Japan.
Print version record.
Keywords: Aesthetics -- Religious aspects; Art and religion; PHILOSOPHY / Religious; Aesthetics -- Religious aspects; Art and religion; PHILOSOPHY / Metaphysics; Electronic books